The Impact of Human Resource Management Practices on Organizational Learning at Jordanian Commercial Banks - Ahmad Zwateen, Islam Ibrahim; Al – Tahitah, Ali Nasser Ali; Al-Mekhlafi, Al-Baraa Abdulrahman; Banyhamdan, Khaled (International Journal of Scientific Research and Management (IJSRM), 2024)
Organizational learning is a critical element that enables an organization to adapt to changes and remain competitive. It allows corporate team members to continue to advance their professional growth and development. This study aimed to investigate the impact of human resources management practices on organizational learning in Jordanian commercial banks. A quantitative method was employed, and the data was collected from the commercial banking sector in Jordan. A total of 386 questionnaires were collected and subjected to analysis. Based on the results, the results that study suggested the presence of a statistically significant effect at the level of significance (α ≤ 0.05) of human resource management practices in their dimensions (employment, training, motivation, performance evaluation) on organizational learning.  The study recommended paying more attention to the hiring process and providing training to new and experienced employees as plans are developed, paying more attention to the hiring process and providing training to new and experienced employees as plans are designed while keeping cross-organizational skills in mind. And pay special attention to the performance evaluation perspective of improving the quality of work.